Visual detection and interpretation of cultural remnants on the Königstuhl hillside in Heidelberg using airborne and terrestrial LiDAR Data - Maack Raun, Karl Hjalte; Pfeiffer, Michelle; Höfle, Bernhard (Digital geoarchaeology, 2018)
LiDAR-based data acquisition, also referred to as laser scanning (LS), is an exceedingly used procedure for investigating site-specific details and spatial context. The main product of LiDAR scanning is digital elevation models (DEMs) derived from recorded 3D point clouds. Two major outcomes of DEMs are digital terrain models (DTM) of the bare earth and digital surface models (DSM) with canopy details. For detection and management of information from the past, especially, the DTM reveals important information for understanding, investigating, and managing sites and landscapes of cultural heritage interest.